IFN-gamma signaling maintains skin pigmentation homeostasis through regulation of melanosome maturation - Natarajan, Vivek T.; Ganju, Parul; Singh, Archana; Vijayan, Vinaya; Kirty, Kritika; Yadav, Shalini; Puntambekar, Shraddha; Bajaj, Sonali; Dani, Prachi P.; Kar, Hemanta K.; Gadgil, Chetan J.; Natarajan, Krishnamurthy; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2014)
Cellular homeostasis is an outcome of complex interacting processes with nonlinear feedbacks that can span distinct spatial and temporal dimensions. Skin tanning is one such dynamic response that maintains genome integrity of epidermal cells. Although pathways underlying hyperpigmentation cascade are recognized, negative feedback regulatory loops that can dampen the activated melanogenesis process are not completely understood. In this study, we delineate a regulatory role of IFN-gamma in skin pigmentation biology. We show that IFN-gamma signaling impedes maturation of the key organelle melanosome by concerted regulation of several pigmentation genes. Withdrawal of IFN-gamma signal spontaneously restores normal cellular programming. This effect in melanocytes is mediated by IFN regulatory factor-1 and is not dependent on the central regulator microphthalmia-associated transcription factor. Chronic IFN-gamma signaling shows a clear hypopigmentation phenotype in both mouse and human skin. Interestingly, IFN-gamma KO mice display a delayed recovery response to restore basal state of epidermal pigmentation after UV-induced tanning. Together, our studies delineate a new spatiotemporal role of the IFN-gamma signaling network in skin pigmentation homeostasis, which could have implications in various cutaneous depigmentary and malignant disorders.
Keywords: detanning; gene regulation; interferon; melanin